2020
DOI: 10.1093/joc/jqaa009
|View full text |Cite
|
Sign up to set email alerts
|

Less Fragmented Than We Thought? Toward Clarification of a Subdisciplinary Linkage in Communication Science, 2010–2019

Abstract: With the explosive growth in research topics, communication science is said to be more fragmented and hyper-specialized than ever before, producing an increasing number of small, niche research topics that lack intellectual coherence as a whole. While such issues have been a central concern for the field, there has been a relative lack of systematic effort to map the topical interconnections among different communication science subfields, answering the question of how they remain empirically fragmented. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…Table 2 contains We performed several exploratory analyses and robustness checks against our methodological and analytic decisions by estimating ITE and additional linear models with covariates (these results are fully reported in the online appendix, Table S8 to S9 Chan & Grill, 2020, Rains et al, 2018, and Song et al, 2020 and whose contact details were listed in ISI Web of Science article record.…”
Section: Preregistered Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 contains We performed several exploratory analyses and robustness checks against our methodological and analytic decisions by estimating ITE and additional linear models with covariates (these results are fully reported in the online appendix, Table S8 to S9 Chan & Grill, 2020, Rains et al, 2018, and Song et al, 2020 and whose contact details were listed in ISI Web of Science article record.…”
Section: Preregistered Main Resultsmentioning
confidence: 99%
“…First, communication is often characterized as a "multidisciplinary field," where the structure and scholarly discourses in the field are vastly heterogeneous (Song et al, 2020;Waisbord, 2019). Second, the introduction and adoption of open science practices are still relatively new within the communication field (see Dienlin et al, 2021;Markowitz et al, 2021) compared to other neighboring disciplines such as psychological science, where the open science movement was widely popularized and expected for publication (see Nosek et al, 2015;Simmons, 2011).…”
Section: Preregistered Main Resultsmentioning
confidence: 99%
“…The dramatic growth in communication scholars and scholarship during the past century has raised important questions about what it means to study human communication (Eadie, 2011;Swanson, 1993;Wartella, 1996). Although narrative histories (e.g., Delia, 1987;Dennis & Wartella, 1996;Sherry, 2004) and empirical examinations (e.g., Günther & Domahidi, 2017;Song, Eberl, & Eisele, 2020) have attempted to answer them, the current study offers a comprehensive look at the field that is data-driven and more expansive than previous works. We present a descriptive account of the topics that animate communication research by examining the abstracts from more than 20,000 articles published in 22 communication journals between 1918 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…This paper provides a tutorial and guide for the Meaning Extraction Method (Chung and Pennebaker, 2008), which is popular in social psychology but rarely applied to communication research. In fact, a search of papers from all International Communication Association journals, National Communication Association journals, and top communication journals indexed by the ISI Web of Science Journal Citation Report (Song et al, 2020) revealed only four articles that mentioned or used the method (LeFebvre et al, 2015;Kim et al, 2016;Stanton et al, 2017;Tong et al, 2020). 3 Half of these papers were written by an author who helped to popularize the method in psychology as well.…”
Section: Introductionmentioning
confidence: 99%